Rotavirus Vaccination and Type 1 Diabetes Risk Among US Children With Commercial Insurance - Burke, Rachel M. (JAMA Pediatr, 2020)
This cohort study uses commercial insurance data to examine the association between rotavirus vaccination and type 1 diabetes incidence.